2003
DOI: 10.1093/heapro/dag414
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the use of maternal health services in rural Bangladesh

Abstract: Utilization of health services is a complex behavioral phenomenon. Empirical studies of preventive and curative services have often found that use of health services is related to the availability, quality and cost of services, as well as to social structure, health beliefs and personal characteristics of the users. In this paper an attempt is made to examine the factors associated with the use of maternal health care services in Bangladesh on the basis of data from a survey of maternal morbidity in Bangladesh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

63
247
4
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(319 citation statements)
references
References 9 publications
63
247
4
5
Order By: Relevance
“…This level of utilization have been said to be influenced by the following factors some of which include; availability, quality and cost of services, as well as social-economic structure, and personal characteristics of the users (Chakraborty et al, 2003;Onah et al 2009). Moreover, Leive and Xu (2008) asserted that a number of factors have been showed to be potential barriers in assessing healthcare services and these include distance and cost of travel to the health facility, socio-cultural factors and cost of service especially in developing countries of the world.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This level of utilization have been said to be influenced by the following factors some of which include; availability, quality and cost of services, as well as social-economic structure, and personal characteristics of the users (Chakraborty et al, 2003;Onah et al 2009). Moreover, Leive and Xu (2008) asserted that a number of factors have been showed to be potential barriers in assessing healthcare services and these include distance and cost of travel to the health facility, socio-cultural factors and cost of service especially in developing countries of the world.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Various studies in developing countries has consistently showed that acquired western education tend to be strongly and positively associated with utilization of healthcare facilities and services (Chakraborty et al, 2003;Kamal, 2009). It has been established that the higher a woman's level of education the more likely she is to utilize maternal healthcare services (MCHS).…”
Section: Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have approached the use of health care services as a behavioral phenomenon (Becker et al, 1993;Chakraborty et al, 2003), while the quality and cost of and access to services are not included. Recently, analysis using the National Family Health Survey -1 (NFHS -1) indicated that community access to health facilities is not an important factor in explaining the utilization of various antenatal care services (Das et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, unskilled persons attend to about 50% of deliveries by Kenyan women [12]. The low utilization of skilled maternal healthcare services has been attributed to cost of service, distance, quality of service, culture, birth order, living conditions of the mother, type of place or residence, level of education, wealth and weak healthcare infrastructure [10,[12][13][14]. Siaya County is one of the counties in Kenya with high maternal mortality ration (MMR) that is above the national average of 495 deaths for every 100,000 live births, with most of these deaths being attributed to home deliveries and low utilization of skilled maternal healthcare services [11].…”
Section: Issn: 2320-5407mentioning
confidence: 99%